2005
DOI: 10.1080/00016480510028546
|View full text |Cite
|
Sign up to set email alerts
|

Clinical feasibility of the new technique of functional 3D laryngeal CT

Abstract: The dynamic vocal fold 3D image during phonation could visualize that the thickness and volume were decreased in relatively to the pitch increase. Typical subglottic shoulder-like image formation and ventricular widening were noted with the high-pitch tone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…and ). To prevent forming only an anterior glottic web, the first suture was placed on the lateral thyroarytenoid muscle, including the low subglottic portion, and the second suture was placed on the vocalis muscle, not including the subglottic portion in one‐third of the membranous vocal folds, which contribute mainly to high‐pitched sound . Two different levels of sutures formed a funnel shape that shortened the anterior one‐third of the membranous vocal fold, and the anterior commissure was relocated to enhance continuous smooth glottic air flow, which is important for a clear voice (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…and ). To prevent forming only an anterior glottic web, the first suture was placed on the lateral thyroarytenoid muscle, including the low subglottic portion, and the second suture was placed on the vocalis muscle, not including the subglottic portion in one‐third of the membranous vocal folds, which contribute mainly to high‐pitched sound . Two different levels of sutures formed a funnel shape that shortened the anterior one‐third of the membranous vocal fold, and the anterior commissure was relocated to enhance continuous smooth glottic air flow, which is important for a clear voice (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[56] Studies have been conducted that have used sequential scans during different phonations. [7] Some of these studies have shown that coronal reconstruction of images acquired during ‘hee’ phonation could improve the detection rate of vocal cord palsy. [8]…”
mentioning
confidence: 99%
“…Furthermore, simulations would have to be performed in patient-specific laryngeal models. In this regard, while the overall geometry of the lumen and the shape and size of the vocal folds can be obtained with reasonable accuracy from high-resolution CT scans (Jun et al, 2005;Kim et al, 2008), it is unlikely that patient-specific information regarding the layered internal structure can be extracted from these scans. Given this limitation, the only available option is to employ a model for the internal a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%